Multidisciplinary surgical team approach for excision of squamous cell carcinoma overlying pacemaker site. (6th February 2018) - Bodagh, Neil; Pappa, Elena; Farooqi, Fahad
Abstract : We report an unusual case of an elderly man presenting with a fast-growing large malignant tumour involving the skin overlying his permanent pacemaker site. The fast-growing cutaneous squamous cell carcinoma appeared 2 years after pacemaker implantation. Joint specialist input was required to tackle this complex problem as a wide surgical excision would expose the pacemaker generator risking device infection particularly if the skin graft reconstruction failed. Having established that the patient had minimal pacing needs, it was determined through expedited multidisciplinary discussion that the best option was excision of the lesion with skin grafting of the defect by maxillofacial surgical team and pacemaker generator removal by a cardiologist in a joint surgical procedure. The procedure was successful and uneventful. This case highlights how effective multidisciplinary planning can help achieve a favourable clinical outcome in a patient with a rare case of a squamous cell carcinoma overlying a pacemaker site.